Analisis Cerpen “Keadilan” Karya Putu Wijaya Menggunakan Pendekatan Mimetik Dan Objektif - Azka Hanifa Sabila; Dani Maulana (Asosiasi Riset Ilmu Pendidikan Indonesia, 2023)
Literary works are works of art that use written language to convey ideas, emotions and experiences through artistic expression. Literary works have various forms such as prose, poetry, drama, short stories, etc. Literary works often have characteristics such as rich language, unique writing style, deep, sharper messages or meanings. A short story is a story essay that has a fictional plot. In researching the short story